Promoting multilingualism through translanguaging in South African classrooms - Mbirimi-Hungwe, Vimbai (Journal for Language Teaching, 2023)
Multilingualism has become a ‘buzz’ term in the academic fora in South Africa and the world at large. Research on multilingualism in South Africa has become ubiquitous, however, academic policies have rendered multilingualism a concealed reality. This paper aims to highlight findings of an inquiry into the existence of multilingual students in an academic literacy class. The paper also intends to bring out how multilingual students utilise their language practices in their mission to understand academic concepts. In this study, students’ perceptions about their multilingual nature are brought to the fore using a qualitative statistical analysis approach. A questionnaire was administered to solicit multilingual students’ views regarding the use of all the languages in their repertoire for academic purposes. The outcome shows that multilingual students benefit more from using a translingual approach to understand academic concepts as opposed to using the code-switching approach. Finally, the study shows that students yearn for the recognition and utilisation of their multilingual nature in their academic endeavours. The paper will respond by suggesting ways in which translingual pedagogy can be used to leverage students’ multilingual habitus.